2020
DOI: 10.1007/s11249-020-01358-x
|View full text |Cite
|
Sign up to set email alerts
|

Fluid Leakage in Metallic Seals

Abstract: Metallic seals are crucial machine elements in many important applications, e.g., in ultrahigh vacuum systems. Due to the high elastic modulus of metals, and the surface roughness which exists on all solid surfaces, if no plastic deformation would occur one expects in most cases large fluid flow channels between the contacting metallic bodies, and large fluid leakage. However, in most applications plastic deformation occurs, at least at the asperity level, which allows the surfaces to approach each other to su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…The study presented in this paper and in Ref. [9,35] shows the importance of plastic flow in some applications to seals. The good agreement found here, and in Ref.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…The study presented in this paper and in Ref. [9,35] shows the importance of plastic flow in some applications to seals. The good agreement found here, and in Ref.…”
Section: Discussionmentioning
confidence: 52%
“…The role of plastic deformation was studied for metallic seals in Ref. [35] where the theory showed that the plastic flow reduce the leakage rate with a factor of ∼ 8, resulting in water leakage rates in good agreement with experiments. We have shown in Ref.…”
Section: Discussionmentioning
confidence: 84%
“…Using the modified C ( q ) from Equation (13) in the method presented above will yield leakages that include the effects of plastic deformation with the given maximal applied pressure. The leakage will be approximately 8 times lower than for purely elastic seals 9 . This is due to the surface height u 1 being only half the size of the undeformed seat.…”
Section: Simulationmentioning
confidence: 91%
“…In other works, the influence of the fluid pressure onto the leakage has been measured and calculated 9 . While the application of only fluid pressure is close to the industrial application, this method measures the result of two different effects.…”
Section: Introductionmentioning
confidence: 99%
“…They are essential (Japanese Industrial Standards [JIS], 2015) and widely applied in industry, machinery, and surroundings. Gaskets prevent the leaking of fluid from various pipe connections and casings onto stationary surfaces (Fischer et al, 2020) of elements. Since a machined surface cannot be absolutely flat, irregularities can be fitted with gaskets between connecting surfaces to ensure that two workpieces are joined closely together.…”
Section: Introductionmentioning
confidence: 99%